Striking variation in chromosome structure within Musa acuminata subspecies, diploid cultivars, and F1 diploid hybrids - Berankova, D.; Cizkova, J.; Majzlikova, G.; Dolezalova, A.; Mduma, H.; Brown, A.; Swennen, R.; Hribova, E. (Frontiers Media, 2024)
The majority of cultivated bananas originated from inter- and intra(sub)specific crosses between two wild diploid species, Musa acuminata and Musa balbisiana. Hybridization and polyploidization events during the evolution of bananas led to the formation of clonally propagated cultivars characterized by a high level of genome heterozygosity and reduced fertility. The combination of low fertility in edible clones and differences in the chromosome structure among M. acuminata subspecies greatly hampers the breeding of improved banana cultivars. Using comparative oligo-painting, we investigated large chromosomal rearrangements in a set of wild M. acuminata subspecies and cultivars that originated from natural and human-made crosses. Additionally, we analyzed the chromosome structure of F1 progeny that resulted from crosses between Mchare bananas and the wild M. acuminata ‘Calcutta 4’ genotype. Analysis of chromosome structure within M. acuminata revealed the presence of a large number of chromosomal rearrangements showing a correlation with banana speciation. Chromosome painting of F1 hybrids was complemented by Illumina resequencing to identify the contribution of parental subgenomes to the diploid hybrid clones. The balanced presence of both parental genomes was revealed in all F1 hybrids, with the exception of one clone, which contained only Mchare-specific SNPs and thus most probably originated from an unreduced diploid gamete of Mchare.